2015
DOI: 10.1128/aem.01585-15
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Carbonate Biomineralization in Biofilms

Abstract: dMicrobially catalyzed precipitation of carbonate minerals is an important process in diverse biological, geological, and engineered systems. However, the processes that regulate carbonate biomineralization and their impacts on biofilms are largely unexplored, mainly because of the inability of current methods to directly observe biomineralization within biofilms. Here, we present a method for in situ, real-time imaging of biomineralization in biofilms and use it to show that Pseudomonas aeruginosa biofilms pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 63 publications
5
51
0
Order By: Relevance
“…Calcium carbonate biomineralization was induced by treating 3-day-old PAO1 biofilms with a supersaturated calcium carbonate medium composed of 15 mM (each) CaCl 2 and NaHCO 3 in 1% TSB at a flow rate of 10 ml/h for 12 h. The medium has a pH of 7.6 and a calcium carbonate saturation index with a log⍀ value of 1.88 at room temperature (ϳ22°C) under atmospheric CO 2 concentrations, yielding the biomineralization of calcium carbonate within the biofilms. We previously showed that this medium is nontoxic to PAO1 biofilms and planktonic cells (29).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calcium carbonate biomineralization was induced by treating 3-day-old PAO1 biofilms with a supersaturated calcium carbonate medium composed of 15 mM (each) CaCl 2 and NaHCO 3 in 1% TSB at a flow rate of 10 ml/h for 12 h. The medium has a pH of 7.6 and a calcium carbonate saturation index with a log⍀ value of 1.88 at room temperature (ϳ22°C) under atmospheric CO 2 concentrations, yielding the biomineralization of calcium carbonate within the biofilms. We previously showed that this medium is nontoxic to PAO1 biofilms and planktonic cells (29).…”
Section: Methodsmentioning
confidence: 99%
“…The biofilms were imaged through the visualization of constitutively expressed green fluorescent protein (GFP). Mineral deposits in the biofilms were imaged by collecting the confocal laser reflectance signal following methods described previously (29).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Virdis et al (2012) demonstrated that CRM allowed monitoring of biofilm development at different growth stages, without impacting its structural or metabolic activity. Li et al (2015) presented CRM for in situ, real-time imaging of the biomineralization in biofilms, through which it was shown that Pseudomonas aeruginosa biofilms could produce morphologically distinct carbonate deposits that substantially modified biofilm structures.…”
Section: Raman Microscopymentioning
confidence: 99%